Awareness of Pediatricians and Family Physicians of the Child Passenger Safety Guidelines in Jeddah, Saudi Arabia - Moroj A. Aldarmasi,; Hadeel S. Alsati,; Naif A. Alkhushi, (Journal of King Abdulaziz University: Medical Sciences, 2021)
The most prevalent obstacle to the utilization of child safety seats is a lack of awareness of their benefits. Recommendations from the American Academy of Pediatrics and other organizations call on physicians to know and promote the health and safety benefits of child safety seats use. The study's objective was to assess the knowledge and self-reported practice of pediatricians and family physicians toward the American Academy of Pediatrics recommendations for child safety seats use. A cross-sectional study was performed in Jeddah, Saudi Arabia, on a target population of pediatricians and family physicians. Data were collected through an electronic self-administered questionnaire. There were 104 respondents; 63% were female, 66% were parents, 63% were pediatricians and 37% were family physicians. Of the respondents, 26.9% had high knowledge, 58.6% had low knowledge and 14.4% had no knowledge. While the level of knowledge varied significantly, older respondents (P=0.025), parents of children (P=0.001) and those with higher professional levels (P=0.007) were more likely to have a higher level of knowledge. Important barriers to child safety seats use are the lack of enforcement laws (67%), large families (53%), and cost (44%). The study shows physicians possess limited knowledge regarding the guidelines for child safety seats use.